Investigation of Optimal PV Allocation to Minimize System Losses and Improve Voltage Stability for Distribution and Transmission Networks Using MATLAB and DigSilent - Rasheed M.A.; Verayiah R. (Frontiers Media S.A., 2023)
Distributed power generation; Electric power factor; Electric power transmission networks; Location; MATLAB; Photovoltaic cells; Solar energy; Stability; Distributed generation units; Fast voltage stability indices; Line stability factor; Optimisations; Photovoltaics; Power factors; Stability factor; System loss; Voltage profile; Voltage-stability index; Genetic algorithms